1988
DOI: 10.1038/336577a0
|View full text |Cite
|
Sign up to set email alerts
|

Localization of an ataxia-telangiectasia gene to chromosome 11q22–23

Abstract: Ataxia-telangiectasia (AT) is a human autosomal recessive disorder of childhood characterized by: (1) progressive cerebellar ataxia with degeneration of Purkinje cells; (2) hypersensitivity of fibroblasts and lymphocytes to ionizing radiation; (3) a 61-fold and 184-fold increased cancer incidence in white and black patients, respectively; (4) non-random chromosomal rearrangements in lymphocytes; (5) thymic hypoplasia with cellular and humoral (IgA and IgG2) immunodeficiencies; (6) elevated serum level of alpha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
244
1
4

Year Published

1995
1995
2016
2016

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 612 publications
(253 citation statements)
references
References 18 publications
4
244
1
4
Order By: Relevance
“…An AT locus (or loci) has been assigned to chromosome 1 lq22-23 [32][33][34]. Complementation studies after mutual fusion of cells from different patients have demonstrated the existence of 4 different AT complementation groups and 2 groups for the related Nijmegen breakage syndrome [35].…”
Section: Discussionmentioning
confidence: 99%
“…An AT locus (or loci) has been assigned to chromosome 1 lq22-23 [32][33][34]. Complementation studies after mutual fusion of cells from different patients have demonstrated the existence of 4 different AT complementation groups and 2 groups for the related Nijmegen breakage syndrome [35].…”
Section: Discussionmentioning
confidence: 99%
“…The gene for ataxia-telangiectasia was mapped to chromosome 11q by genetic linkage analysis in 1988 and was identified by positional cloning in 1995 (Gatti et al, 1988;Savitsky et al, 1995). The gene was called ATM (ataxia-telangiectasia mutated).…”
Section: Ataxia-telangiectasiamentioning
confidence: 99%
“…The A-T gene was initially mapped to chromosome 11q22-23 by Gatti et al (1988) and more recently isolated by positional cloning (Savitsky et al, 1995a). This gene, ATM, occupies 150 kb of genomic DNA and codes for a 13 kb mRNA with an open reading frame of 9.165 kb (Savitsky et al, 1995b;Uziel et al, 1996).…”
Section: Introductionmentioning
confidence: 99%